The physics program of the PADME experiment. (14th January 2022) - Caricato, A P; Martino, M; Oceano, I; Oliva, F; Spagnolo, S; Chiodini, G; Bossi, F; Buonomo, B; De Sangro, R; Di Giulio, C; Domenici, D; Finocchiaro, G; et al.
Abstract: PADME (Positron Annihilation into Dark Matter Experiment) is a fixed target experiment located at the Beam Test Facility (BTF) at the Laboratori Nazionali di Frascati (LNF) designed to search for a massive dark photon A ′ in the process e + e − → γ A ′, using a positron beam of energy up to 550 MeV. The experiment exploits the missing mass technique which allows for a search of A ′ in a model independent way. A sensitivity on the mixing constant ϵ > 10 −3 for a dark photon mass in the range 1 ≤ m A ′ ≤ 23.7 MeV /c 2 can be achieved by collecting 4 × 10 13 positrons on target. Run 2 data taking finished in December 2020 and allowed to reach an integrated luminosity of 5 × 10 12 positrons on target.